Vegetation Density, Root Architecture Model, and Hydrodynamic Simulation Rhizophora apiculata Bl. in Bone Bay, South Sulawesi - Rustam, Aswar; Qayim, Ibnul; Erizal, . (Department of Forest Resources Conservation and Ecotourism - IPB University, 2017)
Mangrove is the only ecosistem that grows and develops in the coastal area. This study was conducted to analyze the mangrove forest vegetation to create a simulation of the root sistem of Rhizophora apiculata Bl. related to its ability in the process of hydrodynamic fluid of seawater in the Lompo village, District Awangpone, Bone Regency, South Sulawesi. Criteria that used as a model reference had minimum age approximately five years and minimum height of about 2 m. The variables that measure were height, diameter, and length of the roots. The parameters of the simulation are the average speed of sea level, the dynamic pressure of seawater, as well as drag coefficient of Gulf of Bone. Based on this research, vegetation area with highest density located at second kilometer, medium density located at first kilometer, and the lowest density located at third kilometer. The average velocity of seawater, the lowest is in the natural cropping pattern of highest density, meanwhile the highest is in the parallel cropping pattern of lowest density. Dynamic pressure, the lowest is in the natural cropping pattern of highest density, meanwhile the highest is in the parallel cropping pattern of lowest density. The drag coefficient, the highest is in the natural cropping pattern of highest density, meanwhile the lowest is in the parallel cropping pattern of lowest density. Keywords: drag coefficient, hydrodynamics, mangrove, Rhizophora apiculata Bl., simulation